2017
DOI: 10.3390/rs9050406
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emissivity in the Detection of Arctic Night Clouds

Abstract: Detection of clouds over polar areas from satellite radiometric measurements in the visible and IR atmospheric window region is rather difficult because of the high albedo of snow, possible ice covered surfaces, very low humidity, and the usual presence of atmospheric temperature inversion. Cold and highly reflective polar surfaces provide little thermal and visible contrast between clouds and the background surface. Moreover, due to the presence of temperature inversion, clouds are not always identifiable as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(75 reference statements)
0
6
1
Order By: Relevance
“…The rainfall-elevation bias correction also shows minimal signal. Contrary to this finding, Romilly and Gebremichael (2011) showed that the accuracy of CMORPH at a monthly time base is related to elevation for six river basins in Ethiopia. A similar finding was reported by Haile et al (2009), Katiraie-Boroujerdy et al (2013), and Wu and Zhai (2012), who found that the performance of CMORPH is affected by elevation.…”
Section: Discussioncontrasting
confidence: 77%
“…The rainfall-elevation bias correction also shows minimal signal. Contrary to this finding, Romilly and Gebremichael (2011) showed that the accuracy of CMORPH at a monthly time base is related to elevation for six river basins in Ethiopia. A similar finding was reported by Haile et al (2009), Katiraie-Boroujerdy et al (2013), and Wu and Zhai (2012), who found that the performance of CMORPH is affected by elevation.…”
Section: Discussioncontrasting
confidence: 77%
“…The threshold was estimated considering both simulated and measured clear sky datasets. The former provides a useful estimate of the threshold value variability around the minimum value calculated from the measured data [23]. Using minimum composites in an operational context can lead to not very accurate results, that is why the suggested approach is the use of radiative transfer model simulations.…”
Section: Hrv Long Term Temporal Testmentioning
confidence: 99%
“…Over land there is cloud masking uncertainty due to land cover and land surface emissivity, which may be temporally and spatially heterogeneous between and within pixels, and elevation, which impacts view angle and atmospheric path. Cloud detection over areas covered by seasonal snow and ice is particularly difficult, especially during nighttime (Frey et al, ; Romano et al, ). Spectral responses for many wavelengths are very similar for snow and ice surfaces compared to clouds.…”
Section: Discussionmentioning
confidence: 99%